Control of cardiac alternans in an electromechanical model of cardiac tissue. (1st August 2015) - Hazim, Azzam; Belhamadia, Youssef; Dubljevic, Stevan
Abstract: Electrical alternations in cardiac action potential duration have been shown to be a precursor to arrhythmias and sudden cardiac death. Through the mechanism of excitation–contraction coupling, the presence of electrical alternans induces alternations in the heart muscle contractile activity. Also, contraction of cardiac tissue affects the process of cardiac electric wave propagation through the mechanism of the so-called mechanoelectrical feedback. Electrical excitation and contraction of cardiac tissue can be linked by an electromechanical model such as the Nash–Panfilov model. In this work, we explore the feasibility of suppressing cardiac alternans in the Nash-Panfilov model which is employed for small and large deformations. Several electrical pacing and mechanical perturbation feedback strategies are considered to demonstrate successful suppression of alternans on a one-dimensional cable. This is the first attempt to combine electrophysiologically relevant cardiac models of electrical wave propagation and contractility of cardiac tissue in a synergistic effort to suppress cardiac alternans. Numerical examples are provided to illustrate the feasibility and the effects of the proposed algorithms to suppress cardiac alternans. Abstract : Highlights: This study presents a novel mechanical perturbation algorithm to control alternans. The control algorithm manipulates the cardiac tissue mechanics to suppress alternans. The proposed algorithm suppresses alternans in relevantly sized cardiac tissues. We alter the action potential duration by perturbing cardiac tissue mechanics.